Legal treatment of the duality of penal legislation in federal countries - a comparative study- - Ismail, Massoud Hamid (Journal of Legal and Political Studies, 2025)
The federal system is based on the division of powers between the federal authorities and the states. Each of them enjoys constitutional independence as well as legislative independence. Therefore, we find that some federal units have their own criminal justice system, including the enactment of penal legislation as well as penal procedures. There is no single model for penal laws and procedures in federal countries. On this basis, some federal countries have adopted the principle of dual criminal laws between the center and the federal states, while others have adopted the principle of the unity of criminal laws and procedures. Since most federal countries have adopted the first principle, these countries have tried to strengthen this principle through several means, both official and unofficial, which we will study in this study Keywords: Duality of penal legislation, federal states, constitutional law
Keywords: Duality of penal legislation; federal states; constitutional law